(untitled) (World Science, 2019)
The article deals with the literary school “Molla Nasreddin” that is considered on the basis of the concrete facts and examples in the context of the principles of the literary school. The main principles of the literary school are highlighted: unity of opinions, clouseness of aesthetic ideals and novelty. The activities of the Azerbaijani satirical journal “Molla Nasreddin”, the first Azerbaijani newspaper “Ekinchi”, (“A ploughman”), the journal “Fuyuzat” (“Admonition”) are traced and appreciated. It is emphasized that the beginning of the XX century is one of the most important stages in the history of Azerbaijani literature. The special attention is given to Jalil Mammadguluzadeh’s activity as a creator of the satirical school “Molla Nasreddin” and founder of critical realism in Azerbaijan. The literary school “Molla Nasreddin” created by him is considered to be a top of satirical literature in Azerbaijan.